The application of non-life insurance ratemaking methods in modelling tax abuses - Leśkiewicz, Marek (Zastosowanie metod taryfikacji ubezpieczeń majątkowych w modelowaniu nadużyć podatkowych, 2019)
In the most general terms, tax evasion is a breach of tax law. Such a practice is characterised by the economic effect of tax burden elimination or reduction. This paper is aimed at adapting the fixed effects models that are applied in the non-life insurance ratemaking process to modelling tax abuses. The common characteristics of tax risk assessment and non-life insurance ratemaking include for both cases: the number of a given type of events is counted in the examined time period, the distribution of the amount levied as a tax liability for a single event is examined, with the distribution characterised by strong right-skewed asymmetry, and finally the expected amount levied as a tax liability on a single insured/entity is estimated based on these results. In the case of insurance ratemaking, the obtained expected value serves directly the purpose of estimating the insurance premium. In the area of tax risk, the obtained expected values serve the purpose of estimating the scale of abuses arising from the application of a given behaviour pattern
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2019, Nr 17 (23), s. 59-70
Keywords: tax abuse; counting variable; compound Poisson distribution; ZIP model; nadużycie podatkowe; zmienna zliczająca; złożony rozkład Poissona; model ZIP